DETERMINANTS OF HIGH FERTILITY AMONG MARRIED WOMEN IN ANGACHA DISTRICT, KAMBETA TEMBERO ZONE, SOUTHERN ETHIOPIA - Abebe, Yosef; Kondale, Mekdes; Jilo, Gemechu Kejela; Hebo, Sultan Hussen; Sidamo, Negussie Boti (Ethiopian Journal of Reproductive Health, 2018)
ABSTRACT BACKGROUND: Fertility is the major component of population dynamics, which is used to show a major role in the size, and structure of a particular population. In Ethiopia, total fertility rate is 4.6 children per woman. This high fertility brings a significant problem on the health of mothers and children. OBJECTIVE: To identify the determinants of high fertility in Angacha District, Southern Ethiopia. METHOD: A community-based case-control study design was conducted from September 20 to October 10, 2017 in Angacha district, Southern Ethiopia. A total of 388 married women in Angacha district were selected using simple random sampling technique. Bi-variable and multi-variable logistic regression analyses were performed. RESULT: A total of 388 eligible women (129 cases and 259 controls) requested to interview, of which 126 cases and 255 controls participated. Educational status of women (AOR[95% CI] = 0.36 [0.160.83]), desire to have more children before marriage (AOR[95% CI] = 0.51[0.28, 0.93]), age at first marriage (AOR[95% CI] = 4.77[2.59, 8.78]), history of under-five mortality (AOR[95% CI] = 4.22[2.43, 7.31]) and not ever use of contraceptive methods (AOR[95% CI] = 4.55[2.21, 9.39]) were identified as determinants of high fertility. CONCLUSION: In this study educational status of women, age at first marriage, desire to have children before marriage, not ever use of contraceptive methods and experiencing under-five mortality were identified as determinants of high fertility. Therefore, all concerned bodies should intervene in improving the education level of women, increase age at first marriage, reduce child mortality and improve the access to contraceptive methods. KEYWORDS: High Fertility, Married Women, Angacha, Southern Ethiopia (Ethiopian Journal of Reproductive Health 2018; 10; 3: 46-54)